Intratumoral microbiota: implications for cancer onset, progression, and therapy - Wu, Jinmei; Zhang, Pengfei; Mei, Wuxuan; Zeng, Changchun (Frontiers in Immunology, 2024)
Significant advancements have been made in comprehending the interactions between the microbiome and cancer. However, prevailing research predominantly directs its focus toward the gut microbiome, affording limited consideration to the interactions of intratumoral microbiota and tumors. Within the tumor microenvironment (TME), the intratumoral microbiome and its associated products wield regulatory influence, directing the modulation of cancer cell properties and impacting immune system functionality. However, to grasp a more profound insight into the intratumoral microbiota in cancer, further research into its underlying mechanisms is necessary. In this review, we delve into the intricate associations between intratumoral microbiota and cancer, with a specific focus on elucidating the significant contribution of intratumoral microbiota to the onset and advancement of cancer. Notably, we provide a detailed exploration of therapeutic advances facilitated by intratumoral microbiota, offering insights into recent developments in this burgeoning field.